(untitled) (Journal of Global Arts Studies, 2024)
Background: The dances of ethnic minority regions in China are a precious treasure in the treasury of Chinese national culture and art. The expressive forms of wedding dances among ethnic minorities in the northwest region are relatively distinctive. Objective: To explore the application significance of artificial intelligence in digital art, and analyze the ethics and value orientation brought by it. Methods: This article will take the wedding dance customs of ethnic minorities in Northwest China as an entry point, and analyze the influencing factors of the body language, expression forms, and cultural composition of wedding dance movements of ethnic minorities in Northwest China. Results: Bringing folk dance art from minority regions to the masses and strengthening cultural construction in minority areas. Conclusion: Promote national unity, achieve common progress, and more actively contribute to the prosperity of minority dance culture.